PENGELOMPOKAN PALA SIAU (Myristica fragrans Houtt) BERDASARKAN KARAKTER BUAH, BIJI, DAN FULI - Runtunuwu, Semuel D.; Mamarimbing, Rinny; Pamandungan, Yefta; Horonis, Seistelin (AGRI-SOSIOEKONOMI, 2022)
This research was conducted to clustering Siau nutmeg based on the characters of fruit weight, fruit length, fruit width, flesh thickness, seed weight, seed length, seed width, and mace weight. The research was conducted using the Survey Method. The survey was conducted in nutmeg gardens owned by farmers in the village: 1) Dompas, 2) Kanawong, 3) Tanaki, 4) Deahe, 5) Bahu, 6) Lagaeng, 7) Dame, 8) Batusenggo, 9) Batubulan, and 10) Pangilolong . Determination of village based on harvested area. The data were analyzed in clusters using the SPSS Statistical Analysis Program. The grouping was done using the agglomerative method. The two most similar populations of nutmeg will be grouped into one, then will be grouped again with other populations that are most similar. Based on the character of the fruit, seeds, and mace, Siau nutmeg can be grouped into three groups. Group 1 consists of Bahu, Lagaeng, Dame, and Batusenggo populations. Nutmeg in these villages has a fruit weight of 55.7 g, an average seed weight of 9.9 g and a mace weight of 1.5 g. Group 2 consisted of Dompas, Kanawong, Tanaki, and Deahe populations. Nutmeg in these villages has a fruit weight of 46.2 g, an average seed weight of 8.3 g, and a mace weight of 1.7 g. Group 3 consisting of Batubulan and Pangilolong populations. Nutmeg in these villages has a fruit weight of 35.80 g, a seed weight of 6.6 g, and a mace of 1.04 g.